Anti-shechita prosecutions in the Anglo-American world, 1855-1913 : "a major attack on Jewish freedoms ..." - Fraser, David, 1953- (North American Jewish studies., 2018)
"This is the first study of historical attempts by anti-animal cruelty groups to prosecute those involved in the killing of animals for food using the Jewish method of slaughter (shechita). It details cases from Australia, Canada, England, Scotland, and the United States, many for the first time, in which animal welfare groups prosecuted those engaged in shechita as part of their attempts to introduce compulsory stunning of animals before slaughter. Despite claims to the contrary, this study offers clear evidence of underlying, unrelenting antisemitic motivations in the prosecutions, and highlights the ways in which a basic idea of innate Jewish cruelty was always juxtaposed with an overtly Christian ideal of humane treatment of animals across time and borders"--